Al-Ghazali’s Framework of Occasionalism in Tahafut al-Falasifah as a Critique of Contemporary Relativism - Muhammad Diaz Supandi; Veli Onan; Junita Rahma Diani (Penerbit Hellow Pustaka, 2026)
The contemporary intellectual landscape is dominated by postmodern relativism, which, by denying universal truth claims and moral values, creates a metaphysical vacuum that fragments public discourse and undermines the foundations of science, ethics, and religion. This crisis stems from a secular worldview that excludes a transcendent ground for reality. Problem: The central problem is the philosophical inadequacy of relativism and the need for a robust metaphysical foundation for objectivity. This research asks how Al-Ghazali's occasionalism can be formulated as a systematic critique of this relativism.This study employs a qualitative library research design, utilizing analytical, interpretative, and constructive methods. It involves a tripartite analysis: reconstructing Al-Ghazali's occasionalism from Tahafut al-Falasifah, deconstructing the internal contradictions of contemporary relativism, and synthesizing the two to build a coherent critique. The research demonstrates that Al-Ghazali's framework, which rejects necessary causality and posits God as the sole Efficient Cause who sustains reality through consistent habits ('adah), provides a viable metaphysical foundation for objectivity. This directly counters the self-referential paradoxes and moral vacuity of relativism by grounding universal order and truth in a Divine Consciousness. The study concludes that Al-Ghazali's occasionalism serves as a powerful metaphysical antidote to contemporary relativism. Its primary contribution is a novel synthesis that bridges classical Islamic and modern philosophy, positioning Al-Ghazali's thought as a living resource for reclaiming objectivity and escaping the postmodern labyrinth.